Relationship between bone mineral density and immune inflammatory parameters in women with osteoporosis concurrent with coronary heart diseases - S. Yu. Tsarenok; V. V. Gorbunov; T. A. Aksenova (Современная ревматология, 2014)
Low bone mineral density (BMD) is a risk factor of osteoporotic fractures. The RANKL–RANK–OPG system and some cytokines are known to play a role in the regulation of bone remodeling. Cytokines and osteoprotegerin (OPG) are able to affect the cardiovascular system. It is highly relevant to study the relationship between BMD and cytokine levels in patients with a concurrence of osteoporosis (OP) and coronary atherosclerosis.Objective: to estimate the relationship between BMD and the level of cytokines and OPG in women having OP comorbid with coronary heart disease (CHD).Subjects and methods. Sixty women (mean age 68.7±8.8 years) with OP comorbid with CHD (Group 1) were examined; a control group consisted of 38 patients (mean age 69.4±8.1 years) with isolated CHD (Group 2). BMD was measured in two regions: lumbar vertebrae (LI–IV) and proximal femur, by employing a DEXA densitometer (CHALLENGER, France). The serum levels of OPG, interleukin (IL) 1β, 4, 6, 8, 10, and tumor necrosis factor (TNF) α were determined by enzyme-linked immunosorbent assay (ELISA).Results. The women with comorbidity were observed to have elevated IL6, 8, TNF-α, IL4, 10, and OPG levels. There was a negative correlation between IL1, TNF-α, and IL8 levels and vertebral BMD; OPG, IL4, 6, 8, and TNF-α concentrations were inversely related to femoral neck BMD. The independent factor of lower BMD was IL6 in the femoral neck and IL1 in the lumbar vertebrae. The findings suggest that there is a relationship between elevated cytokine levels and lower BMD in women having OP comorbid with CHD.